Effects of ceftiofur treatment on the susceptibility of commensal porcine E.coli – comparison between treated and untreated animals housed in the same stable. Issue 1 (December 2015) - Beyer, Anne; Baumann, Sven; Scherz, Gesine; Stahl, Jessica; von Bergen, Martin; Friese, Anika; Roesler, Uwe; Kietzmann, Manfred; Honscha, Walther
Abstract Background Healthy farm animals have been found to act as a reservoir of extended-spectrum β-lactamase (ESBL)-producingEscherichia coli (E. coli). Therefore, the objective of the study was to determine the input of antimicrobial active ceftiofur metabolites in the stable via faeces and urine after intramuscular administration of the drug to pigs and the elucidation of theEscherichia coli ESBL resistance pattern of treated and untreated pigs housed in the same barn during therapy. Methods For determination of the minimal inhibitory concentration (MIC) the method of microdilutionaccording to the recommended procedure of the Clinical and Laboratory Standards Institute was used. Inaddition to that, a qualitative determination was performed by agar dilution. Unsusceptible E. coli speciesselected via agar dilution with cefotaxime were confirmed by MALDI-TOF and ESBL encoding genes wereidentified by PCR. The amounts of ceftiofur measured as desfuroylceftiofur (DFC) in the different probes (plasma, urine, faeces and dust) were analysed by UPLC-MS/MS. Results In a first experiment two groups of pigs (6 animals per group) were housed in the same barn in two separated boxes. One group (group B) were treated with ceftiofur according to the licence (3 mg/kg administered intramuscularly (i.m.) on three consecutive days, day 1–3). During a second treatment period (day 29–31) an increased rate of ESBL resistantE. coli was detectable in these treated pigs and in the air of the stable. Moreover, the second group of animals (group A) formerly untreated but housed for the whole period in the same stable as the treated animals revealed increased resistance rates during their first treatment (day 45–47) with ceftiofur. In order to investigate the environmental input of ceftiofur during therapy and to simulate oral uptake of ceftiofur residues from the air of the stable a second set of experiments were performed. Pigs (6 animals) were treated with an interval of 2 weeks for 3 days with different doses of ceftiofur (3 mg/kg, 1 mg/kg and 0.3 mg/kg i.m.) as well as with 3 mg/kg per os) and the renal and biliary excretion of ceftiofur as its active metabolite were measured in comparison to the plasma levels. In addition to that, probes of the sedimentation dust and the air of the stable were analysed for drug residues. Conclusion The present study shows that treatment of several animals in a stable with ceftiofur influences the resistance pattern of intestinalEscherichia coli of the treated as well as untreated animals housed in the same stable. During therapy with the drug which was administered by injection according to the licence we detected nameable amounts of ceftiofur and its active metabolites in the dust and air of the stable.